# integral

posted by .

find the integral

~(e^x + x)^2 (e^x + 1)dx

can you pls explain how it arrive to this?

ans = 2e^4x + C

• integral -

integral( (e^x+ x)^2 * (e^x + 1) dx )

let u = e^x + x
du = (e^x + 1)dx

Now you have integral(u^2 du)
= (u^3)/3 +C
= ((e^x + x)^3)/3 +C
= (e^3x + 3x*e^2x + 3x^2*e^x + x^3)/3 +C

Are you looking at the right answer key?

## Similar Questions

1. ### Calculus II/III

A. Find the integral of the following function. Integral of (x√(x+1)) dx. B. Set up and evaluate the integral of (2√x) for the area of the surface generated by revolving the curve about the x-axis from 4 to 9. For part …
2. ### Integral

That's the same as the integral of sin^2 x dx. Use integration by parts. Let sin x = u and sin x dx = dv v = -cos x du = cos x dx The integral is u v - integral of v du = -sinx cosx + integral of cos^2 dx which can be rewritten integral …
3. ### calc

how do you start this problem: integral of xe^(-2x) There are two ways: 1) Integration by parts. 2) Differentiation w.r.t. a suitably chosen parameter. Lets do 1) first. This is the "standard method", but it is often more tedious than …
4. ### calc asap!

can you help me get started on this integral by parts?
5. ### Calculus

Find the volume of the solid whose base is the region in the xy-plane bounded by the given curves and whose cross-sections perpendicular to the x-axis are (a) squares, (b) semicircles, and (c) equilateral triangles. for y=x^2, x=0, …
6. ### calculus

LEt f and g be continous functions with the following properties i. g(x) = A-f(x) where A is a constant ii. for the integral of 1 to 2 f(x)dx= the integral of 2 to 3 of g(x)dx iii. for the integral from 2 to 3 f(x)dx = -3A a find the …
7. ### calculus

LEt f and g be continous functions with the following properties i. g(x) = A-f(x) where A is a constant ii. for the integral of 1 to 2 f(x)dx= the integral of 2 to 3 of g(x)dx iii. for the integral from 2 to 3 f(x)dx = -3A a find the …
8. ### math

LEt f and g be continous functions with the following properties i. g(x) = A-f(x) where A is a constant ii. for the integral of 1 to 2 f(x)dx= the integral of 2 to 3 of g(x)dx iii. for the integral from 2 to 3 f(x)dx = -3A a find the …
9. ### Quick calc question

If f(x) and g(x) are continuous on [a, b], which one of the following statements is false?
10. ### Calculus

If f(x) and g(x) are continuous on [a, b], which one of the following statements is true?

More Similar Questions